THE INFLUENCE OF HANGOUT LIFESTYLE ON PURCHASE DECISIONS AT KEKINIAN COFFEE SHOPS IN PALEMBANG STUDENTS - Carolina, Yunita; Rosa Triana Wulandari; Saliyya Elkayyisa Luthfia; Wina Pebriani; Rizq Salsabila Azalia; Khadijah Ramadesfa; Syifa Nurshafia; Beti Firtianingsih; Nabila Amaliah (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2022)
Lifestyle is broadly defined as a way of life that is identified by how a person spends their time (activity), what they consider important in their environment (interest), and what they think about themselves and also the world. around (opinion). Research The purpose of this study was to determine the effect of the hangout lifestyle on purchasing decisions at contemporary coffee shops for college students. The type of research used is quantitative through an associative approach. The sampling technique is non-probability sampling using 50 respondents, namely consumers who have made a purchase at a modern coffee shop at least once. The data collection technique uses a questionnaire on Googleform with a Likert scale of 1-4 with a total of 21 statement items. After the data is collected then perform data analysis techniques. The data analysis technique uses multiple linear regression with the help of SPSS 23.0. The results of this study indicate that the hangout lifestyle (X1) has a significant influence on purchasing decisions. The hangout lifestyle has a simultaneous influence on purchasing decisions in contemporary coffee shops for students.